WORK-LIFE BALANCE KARYAWAN PERUSAHAAN SWASTA DITINJAU DARI PERCEIVED LONG WORKING HOURS DAN PSYCHOLOGICAL SAFETY SAAT BEKERJA DARI RUMAH - Gisela, Fernanda Putri P.; Sumaryono, Sumaryono (Universitas Gunadarma, 2024)
The policy of working from home has bloomed since the global COVID-19 pandemic. New challenges arise when working from home where employees as individuals find it difficult to find the right balance between work and personal life (work-life balance). The influencing factors are excessive workload related to working hours, well-being, and social support related to psychological safety. This study examined the relationship between perceptions of working hours and psychological safety with the work-life balance of employees of private companies who work from home. This study involved 259 participants aged 20-53 years who are private employees who are working from home for at least two weeks. The results show that the perception of working time reduces work-life balance significantly, while psychological safety increases work-life balance significantly